Etiology of Ascites and Pleural Effusion Associated with Ovarian Tumors: Literature Review and Case Reports of Three Ovarian Tumors Presenting with Massive Ascites, but without Peritoneal Dissemination - Ai Miyoshi; Takashi Miyatake; Takeya Hara; Asuka Tanaka; Naoko Komura; Shinnosuke Komiya; Serika Kanao; Masumi Takeda; Mayuko Mimura; Masaaki Nagamatsu; Takeshi Yokoi (Case Reports in Obstetrics and Gynecology)
Borderline ovarian tumors are benign but relatively large tumors that are often initially mistaken as ovarian cancers. We report three cases of stage I borderline ovarian tumors having massive ascites that we (preoperatively) suspected of being advanced ovarian cancer. The three patients (35, 47, and 73 years old) reported feeling fullness of the abdomen before consulting their gynecologist. By CT scan, they were diagnosed with a pelvic tumor accompanied by massive ascites, the diameters of which were 11, 20, and 11 cm, respectively. Postsurgical pathology showed all were stage I borderline ovarian tumors without dissemination; two were mucinous and one was serous. The amount of ascites was 6,300, 2,600, and 3,600 mL, respectively, and was serous in all. Cytodiagnosis of the ascites found that one was positive for tumor cells and two were negative. After resection of the mass, the ascites disappeared in all three cases. No pleural effusion was present at any time. The literature is reviewed concerning ascites and pleural effusions linked to ovarian tumors, and a supposition is forwarded of why pleural effusion presents sporadically in these cases.